PENGUATAN KEPEMIMPINAN ENTREPRENEURIAL PEREMPUAN BERBASIS NILAI-NILAI ISLAM DALAM PENGEMBANGAN KEMANDIRIAN ORGANISASI WANITA NU - Mona Novita (LPPM STAI Muhammadiyah Probolinggo, 2026)
Strengthening women's entrepreneurial leadership based on Islamic values ​​is a strategic need for rural religious organizations in promoting independence and sustainability of empowerment programs. This article aims to analyze the contribution of the Service Learning (SL)-based Community Service (PkM) program in strengthening women's entrepreneurial leadership in the NU Women's Organization in Tirta Mulya Village. The program is designed to be integrated with the Islamic Educational Leadership course and involves students as co-learners and learning facilitators at each SL stage, including pre-service, action/service, reflection, and evaluation. This study uses a descriptive qualitative approach with data collection techniques through participant observation, interviews, reflective discussions, and activity documentation. Data analysis was conducted thematically to identify changes in leadership capacity, community entrepreneurship practices, and organizational governance. The results of the PkM indicate that the implementation of SL effectively drives change at three levels. At the individual level, participants experienced an increased understanding and attitude of entrepreneurial leadership. At the group level, there was increased participation, collaboration, and collective role sharing in community entrepreneurship practices. At the organizational level, there was a shift in orientation from administrative management to a more planned and sustainability-oriented program-based governance. Structured reflection based on Islamic values—such as amanah (trust), deliberation, and muhasabah serves as an ethical foundation that strengthens the legitimacy and accountability of women's entrepreneurial leadership. These findings confirm that service learning not only impacts individual capacity building but also generates capacity development at the organizational level. This article contributes to the development of an integrative, potentially replicable, service learning-based community service model for women's faith-based organizations. It also provides policy implications for universities and the Institute for the Development of Women's Empowerment (LP2M) in mainstreaming service learning as a service strategy based on reflective learning and values.